PRODUÇÃO DE CEBOLA A PARTIR DE BULBINHOS SEMENTE E ANÁLISE ECONÔMICA DO SISTEMA - Camargo, Cristhiano Kopanski (2017)
The research evaluated the performance of 10 commercial onion cultivars (Allium cepa L.) by the method of planting seed bulbs with different crop densities, in the Center-South region of the State of Paraná, regarding the productive and economic characteristics of the crop. The experiments were installed in the Department of Agronomy of the Department of Agronomy of the State University of the Center-West, UNICENTRO, in Guarapuava, PR, using 10 cultivars with precocity characteristics and 4 sowing densities to obtain and evaluate the production of seed bulbs. The results found for the production of seed bulbs indicate that during the two years of evaluation (2014 and 2015), four cultivars stand out for the number of seed bulbs produced, Bella Catarina, Soberana, Lucinda and BR 23. 5 g m-2 was the one that produced the largest number of seed bulbs. It can be concluded that Lucinda, Buccaneer and Soberana had the best performance for plant height with 3,0-3,9 cm diameter bulbs and, Bella Dura, Lucinda, Buccaneer and Soberana, the highest averages of pseudostem diameter when using seed bulbs 3,0-3,9 cm in diameter. The cultivars Sirius, Soberana and Lucinda outstanding ones regarding the production of class 2 bulbs, class 3 and, the total productivity compared to the other cultivars evaluated in the present work when using seed bulbs of 2,0-2,9 and 3,0-3,9 cm in diameter. As for the economic viability of the production of seed bulbs, it can be stated that the exploitation of the onion culture presents economically favorable results, with several indices of economic efficiency. The bulb production system can be used in the rural properties, to produce onion in the off season, and can generate a higher income to the producer.